A Conceptual and Methodological Framework for Psychometric Isomorphism: Validation of Multilevel Construct Measures. (January 2014) - Tay, Louis; Woo, Sang Eun; Vermunt, Jeroen K.
The conceptual and methodological framework for measurement equivalence procedures has been well established and widely used. Although multilevel theories and methods have been widely used in organizational research, there is no comparable framework for measurement equivalence of multilevel constructs, or psychometric isomorphism. In this article, we present a conceptual and methodological framework for understanding and testing various forms of isomorphism. Within this framework, we explicate (a) the different types of psychometric isomorphism, (b) the conditions where psychometric isomorphism is appropriate and necessary, (c) how psychometric isomorphism corresponds with different composition models and estimation methods, and (d) the analytic procedures that can be used. Using simulated data, we also illustrate how the proposed procedures may be applied via two analytic methods—item response theory and factor analysis. We conclude with a discussion of theoretical and methodological implications provided by the proposed framework of psychometric isomorphism.